Kendala dan Rekomendasi Perbaikan Pengembangan Kurikulum di Sekolah Menengah Kejuruan - Wahzudik, Niam (Indonesian Journal of Curriculum and Educational Technology Studies, 2018)
The changes of curriculums always refer to a philosophical thought (idea) and various basic considerations adopted by the schools. The purpose of this study is to fnd out how the implementation of curriculum development in vocational schools is viewed from the aspect of the foundation of curriculum development. The study was carried out with a survey research design. the research sites are in Vocational Schools in Central Java Province. Data collection technique using questionnaires. Quantitative data were analyzed using quantitative descriptive analysis. Whereas qualitative data was interpreted qualitatively to reveal the meaning. The results showed that the curriculum development process in vocational schools was appropriate and already used the foundations of curriculum development. We also found that there was several supports from various stakeholders but still limited, the curriculum development assistance process was not optimal because each school does no has special resources to develop an appropriate and contextual curriculum from curriculum expert. At least we found various problems on the development of school curriculum such as the lack of stakeholder involvement, the poor quality of human resources and the assistance of the curriculum development that are still limited. Abstrak Perubahan dari setiap kurikulum senantiasa mengacu pada suatu pemikiran flosofs (ide) dan berbagai dasar pertimbangan tertentu yang dianut oleh satuan pendidikan. Tujuan penelitian ini adalah untuk mengetahui bagaimanakah pelaksanaan pengembangan kurikulum di Sekolah Menengah Kejuruan (SMK) ditinjau dari aspek landasan pengembangan kurikulum. Penelitian dilaksanakan dengan desain penelitian survei. Tempat penelitian di SMK di wilayah Provinsi Jawa Tengah. Teknik pengumpulan data menggunakan angket. Data yang bersifat kuantitatif dianalisis menggunakan analisis deskriptif kuantitatif, sedangkan data yang bersifat kualitatif akan diinterpretasikan secara kualitatif untuk mengungkap makna yang tersirat di dalamnya. Hasil penelitian menunjukkan bahwa proses pengembangan kurikulum di satuan pendidikan SMK telah sesuai dan menggunakan landasan pengembangan kurikulum, terdapat dukungan dari berbagai stakeholder namun masih terbatas, proses pendampingan kurikulum belum maksimal karena di tiap sekolah tidak ada sumber daya khusus ahli pengembang kurikulum. Berbagai permasalahan dalam pengembangan kurikulum sekolah seperti terbatasnya keterlibatan stakeholder, kualitas sumberdaya manusia dan pendampingan kurikulum yang masih terbatas. Keywords: Curriculum assistance; curriculum development; curriculum expert; human resources; vocational school